Identification of Accident-Prone Locations (Black Spots) Based on Accident Data Approach on La Ode Hadi – M. Brigjen Yoenoes Road, Kendari City - Desy Ariati Syah; Elly Adriani Sinaga; Sri Sarjana (Journal of Social Research, 2025)
Road safety remains a critical issue worldwide, particularly in low- and middle-income countries (LMICs) where the fatality rate from road accidents is significantly high. Excessive vehicle speed (over speeding) is one of the main contributing factors to the increasing frequency and severity of traffic accidents. This study aims to identify accident-prone locations (Black Spots) on La Ode Hadi–M. Brigadier General Yoenoes Road, Kendari City using the Sliding Windows Method combined with the Accident Equivalent Rate (AEK) weighting system based on the Indonesian National Police guidelines. Secondary data were obtained from the Integrated Road Safety Management System (IRSMS) of the National Police, Kendari City Transportation Office, and supporting literature. The analysis shows that along the 4 km road section, there were 36 recorded accidents, dominated by motorcycle collisions (42%) with minor injuries (77%), front–rear collisions (42%) and mostly occur at night (28%). The most accident-prone location identified was the Pasar Baru intersection as segment 11 (Sta 1+100) and 30 (Sta 3+000) with an AEK score of 37 points, exceeding the Black Spot threshold (>30 points). These findings confirm that the Pasar Baru intersection in Kendary City meets the criteria of a Black Spot area, emphasizing the need for targeted safety interventions such as improving the quality of intersection, improving speed management, consistent law enforcement and safety education campaigns to the public to reduce accident risks in urban Kendari.